2008
DOI: 10.1590/s0034-89102008000600009
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados ao envolvimento do pai nos cuidados do lactente

Abstract: OBJECTIVE:To identify factors associated with the lack of active father involvement in infant care at four months of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
11

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 19 publications
0
6
0
11
Order By: Relevance
“…: satisfação conjugal), estão diretamente relacionadas com o envolvimento paterno -quanto menos se consideram eficientes, menos se envolvem com o bebê (Kwok, Ling, Leung, & Li, 2013). Por outro lado, um maior envolvimento por parte do pai parece estar relacionado à boa qualidade dos relacionamentos conjugal e familiar, sendo que a presença de conflitos no casal pode levar a mãe a solicitar e facilitar menos a participação do pai (Falceto et al, 2008;McHale et al, 2004).…”
Section: Discussionunclassified
“…: satisfação conjugal), estão diretamente relacionadas com o envolvimento paterno -quanto menos se consideram eficientes, menos se envolvem com o bebê (Kwok, Ling, Leung, & Li, 2013). Por outro lado, um maior envolvimento por parte do pai parece estar relacionado à boa qualidade dos relacionamentos conjugal e familiar, sendo que a presença de conflitos no casal pode levar a mãe a solicitar e facilitar menos a participação do pai (Falceto et al, 2008;McHale et al, 2004).…”
Section: Discussionunclassified
“…problematic marital relationships and the absence of paternal involvement in child care (27) . In addition, the literature has shown that the absence of social support and the presence of unfavorable relationships between the adolescent mother and her family and/or partner are not only directly related to depressive symptoms, but also to rejection of the child.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal employment is also important. Falceto et al (2008) noted that when mothers did not have a paid job, there was a lower probability of the fathers being involved with their child, than when the mothers were economically active.…”
Section: Factors Affecting Father Involvementmentioning
confidence: 99%
“…Falceto et al (2008), Formoso et al (2007), and Grzybowski and Wagner (2010) found that poor quality marital relationships are associated with low fathering involvement. On the other hand, a constructive alliance between the father and the mother positively infl uenced the quality of the father-child relationsh ip (Formoso et al, 2007).…”
Section: Factors Affecting Father Involvementmentioning
confidence: 99%